Perancangan dan Pengujian Garu Ergonomis bagi Petani Palawija di Sukabumi (Rancangan untuk Petani Perempuan di Desa "SG") - Oki Sunardi (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Many developing countries have their significant income from agricultural or basic industries. Thereafter, many problems in ergonomics started to occur. Researches and activities about ergonomics have arisen since the early of 1960. At the beginning, environmental ergonomics and work physiology were the most selected topics. In India, ergonomics researches began with work physiology, workplace study, design equipment or product, and the manual material handling in agriculture. In China, ergonomics began with information display, signal form in control chamber, and display for instrument. Then, other developing countries have started to implement the ergonomics as a tool to increase and fix productivity and work safety, especially in agriculture and small-scale industries, which man and manual tools are the main actors. These countries are Vietnam, Indonesia, and Thailand. This research found the benefits of implementing ergonomics principles to the design of manual agricultural equipment (the length of bar and the angle of head-rack). Using criteria: biomechanics analysis, psycho-physic analysis, productivity analysis, and energy consumption, the design was tested in the field, with several locally-made rack as comparison. Results found that using the ergonomics design, safety and productivity can be achieved in a significant way.Keywords: Ergonomics, Productivity, Safety